The Financial Times guide to business start up - Williams, Sara (Harlow, England ; New York Prentice Hall, 2006)
Updated for 2006, this is an indispensable guide to starting and running a small business. With sections on getting started, direct marketing, building customer relations, management and accounting, this text is a bible for small businesses.
Age Group: Adult
Includes bibliographical references (p. [407]-418) and index.
Previous ed. published as Lloyds TSB small business guide. London: Press Vitesse, 2003.
Keywords: Start-ups; Business; New Business Enterprises -- Great Britain; Small Business -- Great Britain -- Management